How Jewish Is Jewish History? - Rosman, Moshe (ACLS Humanities E-Book (Series), 2007)
With great vigour and from the vantage point of long experience of writing and teaching Jewish history, Moshe Rosman treats the key questions that postmodernism raises for the writing of Jewish history. What is the relationship between Jewish culture and history and those of the non-Jews among whom Jews live? Can we-in the light of postmodernist thought-speak of a continuous, coherent Jewish People, with a distinct culture and history? What in fact is Jewish cultural history, and how can it be written? How does gender transform the Jewish historical narrative? How does Jewish history fit into t.